Screening Colonoscopy Unmasking Colonic Metastasis from an Occult Breast Ductal Carcinoma: A Case Report and Review of the Literature. (24th February 2019) - Samra, Bachar; Ghanem, Sassine; Ilyas, Ghulam; Taiwo, Evelyn
Abstract : Metastatic spread from breast cancer to the gastrointestinal tract is rare. Such cases are predominantly lobular carcinomas and they usually occur later on during the course of disease progression with the stomach being the most common site involved. Furthermore, occult breast primary tumor is extremely uncommon. To the best of our knowledge, we describe here the first case of incidental colonic metastasis as first presentation of an occult breast ductal carcinoma. We also provide a review of the literature on gastrointestinal—and specifically colonic—involvement from breast ductal carcinoma.